Memórias da primeira turma mista: a inserção das mulheres no Colégio Agrícola Manoel Barata - NASCIMENTO, Damiana Barros do (2018)
This research studies the insertion of women in the first mixed class of the Manoel Barata Agricultural School, current, Federal Institute of Education, Science and Technology of Pará, Castanhal Campus. Even though the Organic Law of Agricultural Education of 1946 has allowed women the right to study agricultural education, the opening of selection process, for both sexes, did not occur at this single federal institution of agricultural education, in the State of Pará. Even with its transfer from Caratateua Island, in Outeiro, to the municipality of Castanhal, in 1972, initially, the insertion was not allowed, having ocurred three years later, precisely, in 1975. The motivation of the research began during analysis of a graduate process, requesting Apprentice Student Time Certificate, in 2015, the year of the fortieth anniversary of this event, without any registration or institutional commemoration. The theoretical-methodological framework of this study is referenced on the historiographical approaches, assumed by Cultural History, in the dynamics of the present time history and linked to the methodological procedure of the oral sources. The work had the participation of twelve people who have in common the experience in the Agricultural School, especially, eight, of the fifteen women inserted in the first mixed class of the Technical Course in Agriculture. The results of analysis of the reports and documents show the challenges and persistence of the first female students during the shared experience in the field and in the classroom, in a College, historically addressed for men. The research shows, through the narratives of the first agricolines, the history of women education, specifically, in agricultural education.